Group Psychoeducation for Relatives of Persons With Bipolar Disorder: Perceived Benefits for Participants and Patients. Issue 9 (September 2015) - Gex-Fabry, Marianne; Cuénoud, Sandrine; Stauffer-Corminboeuf, Marie-Joëlle; Aillon, Nancy; Perroud, Nader; Aubry, Jean-Michel
Abstract : Abstract: Psychoeducation is a key element in the management of patients with bipolar disorders. The present study explored the perception of patients and family members with respect to group psychoeducation for relatives. Patients ( n = 20) and relatives ( n = 26) were assessed with questionnaires about perceived benefits and quality of life (median 4 years after participation). A large majority (>80%) of relatives acknowledged benefits with respect to easier detection of the early warning signs of relapse, improved quality of life, feeling more involved, and engaging in higher quality caregiving activities. Patients were less positive in general, but agreed that the program had helped them deal with crises, increased their feeling of being understood by relatives, and promoted positive changes in the family (>60%). Perceived positive changes in the family were associated with higher quality of life for relatives and patients. The present study highlights the importance of communication enhancement in group psychoeducation for relatives.